Cardiac Glycoside Glucoevatromonoside Induces Cancer Type-Specific Cell Death - Schneider, Naira F. Z.; Cerella, Claudia; Lee, Jin-Young; Mazumder, Aloran; Kim, Kyung Rok; de Carvalho, Annelise; Munkert, Jennifer; Pádua, Rodrigo M.; Kreis, Wolfgang; Kim, Kyu-Won; Christov, Christo; Dicato, Mario; et al. (Frontiers in Pharmacology, 2018)
Cardiac glycosides (CGs) are natural compounds used traditionally to treat congestive heart diseases. Recent investigations repositioned CGs as potential anticancer agents. To discover novel cytotoxic CG scaffolds, we selected the cardenolide glucoevatromonoside (GEV) out of 46 CGs for its low nanomolar anti-lung cancer activity. GEV presented reduced toxicity towards non-cancerous cell types (lung MRC-5 and PBMC) and high-affinity binding to the Na+/K+-ATPase alpha subunit, assessed by computational docking. GEV-induced cell death was caspase-independent, as investigated by a multiparametric approach, and culminates in severe morphological alterations in A549 cells, monitored by transmission electron microscopy, live cell imaging and flow cytometry. This non-canonical cell death was not preceded or accompanied by exacerbation of autophagy. In the presence of GEV, markers of autophagic flux (e.g. LC3I-II conversion) were impacted, even in presence of bafilomycin A1. Cell death induction remained unaffected by calpain, cathepsin, parthanatos or necroptosis inhibitors. Interestingly, GEV triggered caspase-dependent apoptosis in U937 acute myeloid leukemia cells, witnessing cancer-type specific cell death induction. Differential cell cycle modulation by this CG led to a G2/M arrest, cyclin B1 and p53 downregulation in A549, but not in U937 cells. We further extended the anti-cancer potential of GEV to 3D cell culture using clonogenic and spheroid formation assays and validated our findings in vivo by zebrafish xenografts. Altogether, GEV shows an interesting anticancer profile with the ability to exert cytotoxic effects via induction of different cell death modalities.